A versatile and open source design for one and two photon light sheet microscopy - Antoine Hubert; Thomas Panier; Geoffrey Migault; Hugo Trentesaux; Benoît Beaudou; Georges Debrégeas; Volker Bormuth (Scientific Reports)
Abstract Two-photon light sheet microscopy offers great potential for a range of biological applications. Still, its practical implementation is impeded by the high cost of laser sources, the complexity of construction, and the challenges associated with adapting to existing microscope setups. Here, we release an open-source design that addresses these limitations by providing detailed building instructions for transforming a brightfield microscope into a versatile one- and two-photon light sheet system. Our design incorporates a specially designed broadband hollow core fiber, enabling the simultaneous utilization of visible laser alongside an expansive pulsed laser source from another setup. This integration allows for uncompromised image resolution and speed. Furthermore, the design reduces the complexity of construction, alignment, and overall cost, thereby significantly enhancing the accessibility of this technology ( https://github.com/LJPZebra/OLU ).